Summary of Barbara Neiman's Mindfulness & Yoga Skills For Children and Adolescents - Everest Media; Everest Media (Everest Media LLC, 2022)
Please note: This is a companion version & not the original book. Sample Book Insights: #1 Brain Body Tools are strategies for helping kids to gain confidence, relaxation, and self-awareness. They help kids by teaching them how to sense and be kind to others, as well as how information comes to them through both the body and mind. #2 There is concern that children are losing touch with the world around them, as they spend more time with screens. They are not getting enough conversation with adults and one another, and they are not getting enough physical activity, embodied learning, and sensory experiences. #3 The smart board is a dynamic tool for therapy that can be used to display websites, images, and videos. It provides classrooms with opportunities for interactive learning. I have worked with autistic children using the smart board to engage with a yoga DVD. #4 The threefold experience of yoga is slow movements that release tension and are calming for the mind, Pranayama breathing that is regulating by tapping into the parasympathetic nervous system, and asanas that are focusing.